Java concepts - Horstmann, Cay S.
Updated to integrate Java 6, Java Concepts, Fifth Edition introduces you to fundamental programming techniques and design skills that are crucial to learning how to program. Drawing on his many years of experience as an expert programmer and teacher, Horstmann brings out the most important elements of computing, problem solving, and program design